2020
DOI: 10.1002/advs.201903680
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Energy Conversion and Storage Based on Robust Fluoride‐Free Self‐Assembled 1D Niobium Carbide in 3D Nanowire Network

Abstract: 2D materials have drawn tremendous attention and extensive investigations for emerging applications in energy, electronics, and optoelectronics have been conducted. [1,2] In particular, 2D transition metal carbides and nitrides (MXenes) are considered as emerging energy materials. Enjoying their endowments in the high hydrophilic surface, porosity, and conductivity, MXenes possess widespread applications in battery, electrocatalyst, supercapacitor, and biochemistry. [3][4][5][6][7] MXenes are usually described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 49 publications
2
43
0
Order By: Relevance
“…With strong stirring, the parent phase MAX creates gaps on the TiC surface and splits into small pieces, the lateral size of which is reduced from 10 ~ 30 to 1 ~ 5 μm. Under ultrasonic treatment, a shorter etching time can make the MAX-MXene composite produce nanowire "shred effect" [77].…”
Section: Chemical Exfoliationmentioning
confidence: 99%
“…With strong stirring, the parent phase MAX creates gaps on the TiC surface and splits into small pieces, the lateral size of which is reduced from 10 ~ 30 to 1 ~ 5 μm. Under ultrasonic treatment, a shorter etching time can make the MAX-MXene composite produce nanowire "shred effect" [77].…”
Section: Chemical Exfoliationmentioning
confidence: 99%
“…In consideration of the potential toxic property of the intercalants, Hao and co-workers proposed a universal thermal-assisted electrochemical etching route in HCl electrolyte. [164,165] The mild heating could boost the etching speed. Various MXenes such as Ti 2 CT x , Cr 2 CT x , V 2 CT x , and Nb 2 CT x were successfully fabricated using this method.…”
Section: Electrochemical Methodsmentioning
confidence: 99%
“…[158,159] However, mechanical exfoliation of MAX phase is hardly possible due to the strong interlayer chemical bonds between M and A. [160] To date, a lot of synthesis strategies for MXene have been reported, which mainly contains etching by fluoride-based aqueous solutions (such as HF, LiF + HCl mixtures, and NH 4 HF 2 ), [161] electrochemical method, [162][163][164][165] alkali-assisted hydrothermal method, [166] water-free etching in polar organic solvents, [167] molten salt etching method, [168][169][170] salt-templated method, [171] thermal reduction method, [172] and chemical vapor deposition (CVD) method. [173]…”
Section: (6 Of 30)mentioning
confidence: 99%
“…[44] Besides the high-temperature molten salts and CVD methods, electrochemical etching is an alternative HF-free method. [45,46] Because Al is more easily oxidized than Ti, Al in the Ti 3 AlC 2 MAX phase can be selectively removed through electrochemical etching. Sun et al reported the etching of A-layers from the MAX phase in hydrochloric acid for 120 h at 0.6 V versus Ag/AgCl to form Ti 2 CT x .…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…Ti 2 CT x , V 2 CT x , Cr 2 CT x , and Nb 2 CT x are obtained by the electrochemical etching method and show superior elctrocatalytic performance. [45,46] However, more MXenes (M n+1 X n T x ) with different M and n should be investigated using this method. The molten salts etching method is also efficient for producing MXenes with F or Cl termination without using toxic reagents.…”
Section: Materials Synthesismentioning
confidence: 99%